A fluorine-free oil-proofing agent, preparation method and application in pulp molding manufacturing
By preparing modified fillers and composite emulsions, the problem of poor binding performance of fluorine-free oil-proofing agents in pulp molded products is solved, better oil-proofing performance and thermal stability are achieved, and application stability and high-temperature oil-proofing performance are improved.
Patent Information
- Application Number
- CN202411697329.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing fluorine-free oil-proofing agents have poor binding performance in pulp molded products, resulting in insufficient oil-proofing performance and thermal stability, and poor application stability. The oil-proofing effect gradually decays during storage.
By preparing modified fillers, binary composite treatment and ternary composite treatment, the modified fillers and composite emulsions are formed by combining zirconium-doped HKUST-1 material with aldehyde-based modification, silicon source and crosslinked monomer, to improve the binding performance and oil resistance of fluorine-free oil-proof agent and pulp molding slurry, and to improve its performance in high temperature environment.
The combination performance and oil resistance of fluorine-free oil-proofing agent with pulp molding slurry are significantly improved, the thermal deformation problem is avoided, and good physical properties and oil resistance are maintained in high-temperature environments or contact with high-temperature foods, while improving application stability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of fluorine-free oil-proofing agents, in particular to a fluorine-free oil-proofing agent, a preparation method and application thereof in pulp molding manufacturing. Background Art
[0002] At present, with the continuous improvement of living standards and the accelerated pace of daily work, fast food and take-out have become convenient choices for most people, but it has also led to an increasing consumption of take-out boxes; especially disposable fast food boxes made of plastic are widely used. However, disposable fast food boxes made of this type of material cannot be naturally decomposed, and the recycling rate is low. Discarded disposable fast food boxes can be seen everywhere, which is not environmentally friendly. With the continuous enhancement of environmental awareness, the development of environmentally friendly biomass materials has become the main direction of the current green packaging industry; and pulp molded products, as one of the ideal choices to replace plastic lunch boxes, have gradually become a current research hotspot. "Replacing plastic with paper" can not only make full use of plant fiber raw materials that are abundant in the natural environment, low in price, and have a short regeneration cycle, but also the paper tableware produced is easy to degrade and reusable, so it is considered to be the most effective substitute for plastic lunch boxes.
[0003] Pulp molding is a three-dimensional papermaking technology that uses primary plant fibers or secondary plant fibers as the main raw materials, specifically bagasse pulp, bamboo pulp and other plant fibers as raw materials. After pulping, grinding, slurry mixing and other processes, the pulp molding machine passes through the mold vacuum suction filtration molding, hot pressing drying and shaping processes, and finally obtains a paper product with a specific geometric cavity structure. In order to give pulp molding waterproof and oil-proof properties, pulp molding is usually treated with fluorine-based oil-proof agents, such as perfluorooctanoic acid oil-proof agents, perfluorooctane sulfonyl oil-proof agents, etc. However, fluorine-based oil-proof agents have poor environmental friendliness and there is persistent organic pollution; and there are potential risks to human health during the production process. Therefore, fluorine-free oil-proof agents are gradually replacing fluorine-based oil-proof agents with their non-toxic and environmentally friendly characteristics.
[0004] Existing fluorine-free oil-proofing agents generally use paraffin and starch as main raw materials. Although they can impart certain oil-proofing properties to pulp molded products in their oil-proofing applications, in actual applications, the fluorine-free oil-proofing agents have poor bonding properties with pulp molding slurries and are unable to stably bond within the pores of the fiber network of pulp molding, which not only affects the oil-proofing properties of pulp molded products, but also leads to poor thermal stability of pulp molded products, resulting in thermal deformation when heated, and being unable to maintain proper physical properties and oil-proofing properties in high-temperature environments or after contact with high-temperature foods.
[0005] Furthermore, the application stability of fluorine-free oil-proofing agents is poor. After adding fluorine-free oil-proofing agents to pulp molding slurry, the oil-proofing effect will gradually decay as the storage time of the slurry increases (generally, performance decay occurs after 2 hours of storage), and the ideal oil-proofing effect cannot be maintained in the slurry for a long time. Summary of the invention
[0006] In order to solve the technical problems existing in the prior art, the present invention provides a fluorine-free oil-proofing agent, a preparation method and an application in pulp molding manufacturing, which can effectively improve the bonding performance of the fluorine-free oil-proofing agent and the pulp molding slurry, improve the oil-proofing performance of the pulp molded products after application, and avoid the problem of thermal deformation, and can preserve good physical properties and oil-proofing performance in a high temperature environment or after contact with high-temperature food; and improve the application stability of the fluorine-free oil-proofing agent in the pulp molding slurry.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a fluorine-free oil-proofing agent comprises the following steps: preparing a modified filler, a binary composite treatment, a ternary composite treatment, and a mixed preparation.
[0009] The method for preparing the modified filler comprises the following steps: adding zirconium nitrate pentahydrate and copper nitrate trihydrate into deionized water, stirring and dissolving them, and then adding calcium carbonate and montmorillonite, stirring for 10-20 minutes to obtain a first dispersion; adding trimesic acid into anhydrous ethanol, stirring and dissolving them, and obtaining a second dispersion; adding the first dispersion and the second dispersion into a high-pressure reactor, sealing the high-pressure reactor, stirring and heating to 70-75° C., keeping the temperature and stirring for reaction for 4-5 hours, cooling naturally to room temperature, and centrifuging to obtain a The solid is washed with anhydrous ethanol and deionized water, placed in a vacuum thermostat, and activated at 120-130° C. for 5-6 hours under a vacuum degree of 0.02-0.03 MPa to obtain a primary modified filler; the primary modified filler is put into a 40-45 times weight of glutaraldehyde aqueous solution (concentration of 4.5-4.8wt%), ultrasonically treated for 30-40 minutes at room temperature, and a solid is obtained by centrifugation, and the solid is washed with deionized water and then dried to obtain a modified filler.
[0010] In the preparation of the modified filler, in the first dispersion, the weight ratio of zirconium nitrate pentahydrate, copper nitrate trihydrate, deionized water, calcium carbonate, and montmorillonite is 1.1-1.2:3.5-3.7:100-105:7-7.5:4-4.2;
[0011] In the second dispersion, the weight ratio of trimesic acid to anhydrous ethanol is 3.9-4.1:100-105;
[0012] The weight ratio of the first dispersion to the second dispersion is 1:1-1.1.
[0013] In the preparation of the modified filler, the ultrasonic treatment frequency is 20-22 KHz, and the ultrasonic treatment intensity is 12-13 W / cm 2 , the ultrasonic treatment power is 350-400W, and the ultrasonic treatment time is 30-40min.
[0014] The binary composite treatment method comprises the following steps: adding the modified filler and the emulsifier OP-10 into deionized water, stirring for 20-30 minutes, heating to 65-70° C. with stirring, adding butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide and vinyltriethoxysilane with keeping the temperature and stirring for 10-20 minutes, and then dripping an aqueous solution of ammonium persulfate with a concentration of 5-6wt%; after the dripping is completed, continuing to keep the temperature and stirring for 3-3.5 hours to obtain a binary composite emulsion.
[0015] In the binary composite treatment, the weight ratio of modified filler, emulsifier OP-10, deionized water, butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide, vinyl triethoxysilane, and ammonium persulfate aqueous solution is 16-17:2.5-2.8:80-85:14-15:10-10.5:3.2-3.5:5.7-6:10-12.
[0016] The method of the ternary composite treatment is as follows: adding the modified chitosan into 120-130 times the weight of the binary composite emulsion, stirring and heating to 42-45° C., and keeping warm; controlling the ultrasonic frequency to 25-28 KHz, the ultrasonic power to 350-400 W, the stirring speed to 70-80 rpm, and performing ultrasonic stirring reaction for 5-6 hours to obtain the ternary composite emulsion.
[0017] The preparation method of the modified chitosan comprises the following steps: adding chitosan with a viscosity average molecular weight of 300,000 to 400,000 to an acetic acid aqueous solution with a volume concentration of 1.2 to 1.5%, stirring to dissolve, stirring and heating to 45 to 50° C. in a nitrogen atmosphere, and keeping the temperature; adding potassium persulfate, and keeping the temperature and stirring for 5 to 10 minutes; then adding glycidyl trimethylammonium chloride and N-vinyl formamide at the same time, keeping the temperature and stirring for 5 to 6 hours to obtain a reaction solution; stirring and adding acetone with a volume of 60 to 70% of the reaction solution, continuing to stir for 20 to 30 minutes, and centrifuging to obtain a solid; washing the solid with deionized water, placing it in a vacuum thermostat, and drying it to a constant weight at 80 to 85° C. under a vacuum degree of 0.08 to 0.09 MPa to obtain the modified chitosan.
[0018] In the preparation of the modified chitosan, the weight ratio of chitosan, acetic acid aqueous solution, potassium persulfate, glycidyl trimethylammonium chloride and N-vinyl formamide is 1.9-2.2:100-110:0.7-0.8:3.2-3.5:2.4-2.6.
[0019] The mixed preparation method comprises the following steps: heating food-grade paraffin to be completely melted to obtain melted food-grade paraffin for standby use; adding cationic starch into deionized water, stirring and heating to 70-75°C, keeping the temperature and stirring for 20-30 minutes, stirring and adding melted food-grade paraffin, keeping the temperature and stirring for 40-50 minutes, continuing to stir and adding ternary composite emulsion, stirring for 10-20 minutes, placing in a high-pressure homogenizer, controlling the homogenization pressure to be 10-11MPa, the homogenization speed to be 4500-5000rpm, performing high-pressure homogenization for 10-15 minutes, cooling to room temperature, and obtaining a fluorine-free oil repellent.
[0020] In the mixed preparation, the weight ratio of food-grade paraffin, cationic starch, deionized water and ternary composite emulsion is 33-36:12-13:64-67:7-8.
[0021] A fluorine-free oil-proofing agent is prepared by the above-mentioned preparation method.
[0022] An application of the above-mentioned fluorine-free oil-proofing agent in pulp molding manufacturing.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) In the preparation method of the fluorine-free oil-proofing agent of the present invention, in the step of preparing the modified filler, the fluorine-free oil-proofing agent filler component (calcium carbonate, montmorillonite) is used in combination with a zirconium source and a copper source to prepare a zirconium-doped HKUST-1 material, and a primary modified filler composited with the filler component and the zirconium-doped HKUST-1 material is obtained by in-situ composite method, and then the primary modified filler is subjected to aldehyde group modification to obtain a modified filler; the modified filler after composite filling the voids of the pulp molded product and the combination of the modified filler and the pulp molded product promote the formation of a dense barrier layer of the fluorine-free oil-proofing agent; and at the same time, the stability of the fluorine-free oil-proofing agent in the pores of the fiber network of the pulp molded product is improved. , improve the thermal stability and physical properties of pulp molding; and improve the reaction and bonding performance of the modified filler with other components in the subsequent steps through aldehyde modification; then in the binary composite treatment step, the modified filler, silicon source (vinyl triethoxysilane) and cross-linking monomer (N, N-dimethyl methacrylamide) are used in the polymerization preparation of polyacrylate emulsion, and the aldehyde groups on the surface of the modified filler are reacted and composited with the polymer macromolecules, and the adsorption and interface effects of the modified filler on the polymer macromolecules are further improved. At the same time, the silicon source (vinyl triethoxysilane) and the cross-linking monomer (N, N-dimethyl methacrylamide) are combined to form a polyacrylate emulsion. The invention discloses a novel ternary composite emulsion comprising a polyacrylic acid amine (hereinafter referred to as amine) and a polyacrylic acid ester emulsion, and further improves the cross-linking film-forming and bonding performance of the binary composite emulsion on the surface of each fiber inside the pulp molding, further improves the oil-proof performance after application, and improves the weather resistance and structural stability of the pulp molding product, avoids the problem of its thermal deformation and thermal physical property degradation, and improves the storage stability in the slurry after the application of the fluorine-free oil-proof agent; then in the ternary composite treatment step, after the modified chitosan is modified by using a specific cationic monomer and a non-ionic monomer, the modified chitosan is contacted with the binary composite emulsion, and through chemical bonding and electrostatic action, it is further compounded into a ternary composite emulsion, and further improved. The barrier and oil-proof properties of the fluorine-free oil-proof agent are high; and the thermal stability and structural stability of the pulp molded products are improved by combining modified chitosan with the aforementioned binary components; finally, the ternary composite emulsion is used in combination with paraffin and starch to prepare the fluorine-free oil-proof agent. The aforementioned technical means cooperate and work synergistically with each other to effectively improve the bonding performance of the fluorine-free oil-proof agent with the pulp molding slurry, while improving the oil-proof properties of the pulp molded products after application, avoiding its thermal deformation problem, being able to preserve good physical properties in a high temperature environment or after contact with high temperature food, and improving the high temperature oil-proof properties of the pulp molded products; and improving the application stability of the fluorine-free oil-proof agent in the slurry.
[0025] (2) After the fluorine-free oil-proofing agent of the present invention is mixed with the pulp molding slurry, the pulp molding product (thickness 0.8mm, basis weight 400g / m 2 ) has a ring compression strength index of 13.8-13.9 N·m / g, Taber stiffness of 21.2-21.5 mN·m, and a burst resistance index of 3.5-3.6 (kPa·m2 ) / g, tightness is 0.84-0.85g / cm 3 The oil resistance grade of pulp molded products is 10, the contact angle of castor oil is 96-97°, and 120°C hot oil is left on the pulp molded surface for 120 minutes without hot oil penetration or diffusion.
[0026] (3) After the fluorine-free oil-proofing agent of the present invention is mixed with the pulp molding slurry, the pulp molding product (thickness 0.8mm, basis weight 400g / m 2 ) was filled with 120 hot oil and kept at 120℃ for 8h without thermal deformation. At the same time, after the pulp molded products were kept at 150℃ for 24h, no thermal deformation occurred. Moreover, after being kept at 150℃ for 24h, the ring compression strength index of the pulp molded products could still reach 13.2-13.3N·m / g, the Taber stiffness could still reach 20.3-20.7mN·m, and the burst resistance index could still reach 3.2-3.4 (kPa·m 2 ) / g, the tightness can still reach 0.81-0.82g / cm 3 The oil resistance grade of pulp molded products can still reach grade 10, and the contact angle of castor oil can still reach 93-94°. The fluorine-free oil-proof agent has good bonding performance with pulp molding slurry, and the prepared pulp molded products have good thermal stability and can maintain good physical properties and oil resistance in high temperature environment or after contact with high temperature food.
[0027] (4) The fluorine-free oil-proofing agent of the present invention is mixed with the pulp molding slurry and stored for 8 hours, and then pulp molding is performed to prepare the pulp molding product (thickness 0.8mm, basis weight 400g / m 2 ) can still reach 13.8N·m / g, Taber stiffness can still reach 21.3mN·m, and burst resistance index can still reach 3.5 (kPa·m 2 ) / g, the tightness can still reach 0.84g / cm 3 The oil-proof grade of pulp molding products can still reach grade 10, and the contact angle of castor oil can still reach 97°. The application stability of fluorine-free oil-proof agent is good, which can avoid the problem of oil-proof effect attenuation during static storage after the fluorine-free oil-proof agent is added to the pulp molding slurry. DETAILED DESCRIPTION
[0028] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0029] Example 1
[0030] This embodiment provides a method for preparing a fluorine-free oil repellent, specifically:
[0031] 1. Preparation of modified fillers
[0032] Zirconium nitrate pentahydrate and copper nitrate trihydrate are added to deionized water, stirred and dissolved, and then calcium carbonate and montmorillonite are added and stirred for 10 minutes to obtain a first dispersion; trimesic acid is added to anhydrous ethanol, stirred and dissolved to obtain a second dispersion; the first dispersion and the second dispersion are added to a high-pressure reactor, the high-pressure reactor is sealed, the temperature is raised to 70°C with stirring, the reaction is kept stirring for 4 hours, and then naturally cooled to room temperature, and solids are obtained by centrifugation; the solids are washed with anhydrous ethanol and deionized water, placed in a vacuum thermostat, and activated at 120°C for 5 hours under a vacuum degree of 0.02MPa to obtain a primary modified filler; the primary modified filler is added to 40 times the weight of a glutaraldehyde aqueous solution (concentration of 4.5wt%), ultrasonically treated for 30 minutes under room temperature, and solids are obtained by centrifugation, and the solids are washed with deionized water and dried to obtain a modified filler.
[0033] In the first dispersion, the weight ratio of zirconium nitrate pentahydrate, copper nitrate trihydrate, deionized water, calcium carbonate and montmorillonite is 1.1:3.5:100:7:4.
[0034] In the second dispersion, the weight ratio of trimesic acid to anhydrous ethanol is 3.9:100.
[0035] The weight ratio of the first dispersion liquid to the second dispersion liquid is 1:1.
[0036] The ultrasonic treatment frequency was 20KHz and the ultrasonic treatment intensity was 12W / cm 2 , the ultrasonic treatment power is 350W.
[0037] 2. Binary composite treatment
[0038] The modified filler and emulsifier OP-10 were added to deionized water, stirred for 20 minutes, then heated to 65°C with stirring, and butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide and vinyltriethoxysilane were added with stirring while keeping warm. After keeping warm and stirring for 10 minutes, a 5wt% aqueous solution of ammonium persulfate was added dropwise. After the addition was completed, the reaction was continued with keeping warm and stirring for 3 hours to obtain a binary composite emulsion.
[0039] Wherein, the weight ratio of modified filler, emulsifier OP-10, deionized water, butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide, vinyl triethoxysilane and ammonium persulfate aqueous solution is 16:2.5:80:14:10:3.2:5.7:10.
[0040] 3. Ternary composite treatment
[0041] The modified chitosan was added into 120 times the weight of the binary composite emulsion, and the temperature was raised to 42°C with stirring, and kept warm; the ultrasonic frequency was controlled to 25KHz, the ultrasonic power was 350W, and the stirring speed was 70rpm, and the ultrasonic stirring reaction was carried out for 5 hours to obtain the ternary composite emulsion.
[0042] The preparation method of modified chitosan is as follows: chitosan with a viscosity-average molecular weight of 300,000 is put into an acetic acid aqueous solution with a volume concentration of 1.2%, and after stirring to dissolve, the mixture is heated to 45°C in a nitrogen atmosphere and kept warm; potassium persulfate is added, and the mixture is stirred and kept warm for 5 minutes; then trimethylammonium glycidyl chloride and N-vinylformamide are added simultaneously, and the mixture is stirred and kept warm for 5 hours to obtain a reaction solution; acetone with a volume of 60% of the reaction solution is added under stirring, and stirring is continued for 20 minutes, and solid matter is obtained by centrifugation; the solid matter is washed with deionized water, and then placed in a vacuum thermostat, and dried to constant weight at 80°C under a vacuum degree of 0.08 MPa to obtain modified chitosan.
[0043] The weight ratio of chitosan, acetic acid aqueous solution, potassium persulfate, glycidyl trimethylammonium chloride and N-vinylformamide is 1.9:100:0.7:3.2:2.4.
[0044] 4. Mixed preparations
[0045] Heat food-grade paraffin until it is completely melted to obtain molten food-grade paraffin for standby use; add cationic starch into deionized water, stir and heat to 70°C, keep warm and stir for 20 minutes, stir and add molten food-grade paraffin, keep warm and stir for 40 minutes, continue to stir and add ternary composite emulsion, stir for 10 minutes, place in a high-pressure homogenizer, control the homogenization pressure to 10MPa, the homogenization speed to 4500rpm, perform high-pressure homogenization for 10 minutes, cool to room temperature, and obtain a cationic fluorine-free oil repellent.
[0046] Among them, the weight ratio of food-grade paraffin, cationic starch, deionized water and ternary composite emulsion is 33:12:64:7.
[0047] The present embodiment also provides a fluorine-free oil repellent prepared by the aforementioned preparation method. After product qualification testing, the fluorine-free oil repellent of the present embodiment has an active ingredient content greater than 35wt%, a viscosity (25°C) ≤300mPa·s, and a pH (25°C) in the range of 3.0-6.0.
[0048] This embodiment also provides the use of the aforementioned fluorine-free oil-proofing agent in pulp molding manufacturing, specifically, the aforementioned fluorine-free oil-proofing agent is mixed with pulp molding slurry to prepare pulp molding.
[0049] Wherein, the added weight of the fluorine-free oil-proofing agent is 1% of the weight of the pulp molding slurry.
[0050] Example 2
[0051] This embodiment provides a method for preparing a fluorine-free oil repellent, specifically:
[0052] 1. Preparation of modified fillers
[0053] Zirconium nitrate pentahydrate and copper nitrate trihydrate are added to deionized water, stirred and dissolved, and then calcium carbonate and montmorillonite are added and stirred for 15 minutes to obtain a first dispersion; trimesic acid is added to anhydrous ethanol, stirred and dissolved to obtain a second dispersion; the first dispersion and the second dispersion are added to a high-pressure reactor, the high-pressure reactor is sealed, and the temperature is raised to 72°C with stirring, and the reaction is kept stirring for 4.5 hours, and then naturally cooled to room temperature, and centrifuged to obtain a solid; the solid is washed with anhydrous ethanol and deionized water, and then placed in a vacuum thermostat, and activated at 125°C for 5.5 hours under a vacuum degree of 0.025 MPa to obtain a primary modified filler; the primary modified filler is added to 43 times the weight of a glutaraldehyde aqueous solution (concentration of 4.7wt%), and ultrasonically treated for 35 minutes at room temperature, and then centrifuged to obtain a solid, and the solid is washed with deionized water and dried to obtain a modified filler.
[0054] Among them, in the first dispersion, the weight ratio of zirconium nitrate pentahydrate, copper nitrate trihydrate, deionized water, calcium carbonate and montmorillonite is 1.15:3.6:103:7.2:4.1.
[0055] In the second dispersion, the weight ratio of trimesic acid to anhydrous ethanol is 4:103.
[0056] The weight ratio of the first dispersion liquid to the second dispersion liquid is 1:1.05.
[0057] The ultrasonic treatment frequency was 21KHz and the ultrasonic treatment intensity was 12.5W / cm 2 , the ultrasonic processing power is 370W.
[0058] 2. Binary composite treatment
[0059] The modified filler and emulsifier OP-10 were added to deionized water, stirred for 25 minutes, then heated to 68°C with stirring, and butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide and vinyltriethoxysilane were added with stirring while keeping warm. After keeping warm and stirring for 15 minutes, a 5.5wt% aqueous solution of ammonium persulfate was added dropwise. After the addition was completed, the reaction was continued with keeping warm and stirring for 3.2 hours to obtain a binary composite emulsion.
[0060] Wherein, the weight ratio of modified filler, emulsifier OP-10, deionized water, butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide, vinyl triethoxysilane and ammonium persulfate aqueous solution is 16.5:2.7:83:14.5:10.3:3.4:5.9:11.
[0061] 3. Ternary composite treatment
[0062] The modified chitosan was added into 125 times the weight of the binary composite emulsion, and the temperature was raised to 44°C with stirring, and kept warm; the ultrasonic frequency was controlled to 26KHz, the ultrasonic power was 380W, and the stirring speed was 75rpm, and the ultrasonic stirring reaction was carried out for 5.5 hours to obtain the ternary composite emulsion.
[0063] The preparation method of modified chitosan is as follows: chitosan with a viscosity-average molecular weight of 350,000 is put into an acetic acid aqueous solution with a volume concentration of 1.4%, and after stirring to dissolve, the mixture is heated to 48°C in a nitrogen atmosphere and kept warm; potassium persulfate is added, and the mixture is kept warm and stirred for 8 minutes; then trimethylammonium glycidyl chloride and N-vinylformamide are added simultaneously, and the mixture is kept warm and stirred for 5.5 hours to obtain a reaction solution; acetone with a volume of 65% of the reaction solution is added under stirring, and stirring is continued for 25 minutes, and solid matter is obtained by centrifugation; the solid matter is washed with deionized water, and then placed in a vacuum thermostat, and dried to constant weight at 82°C under a vacuum degree of 0.085 MPa to obtain modified chitosan.
[0064] The weight ratio of chitosan, acetic acid aqueous solution, potassium persulfate, glycidyl trimethylammonium chloride and N-vinyl formamide is 2.1:105:0.75:3.3:2.5.
[0065] 4. Mixed preparations
[0066] Heat food-grade paraffin until it is completely melted to obtain molten food-grade paraffin for standby use; add cationic starch into deionized water, stir and heat to 72°C, keep warm and stir for 25 minutes, stir and add molten food-grade paraffin, keep warm and stir for 45 minutes, continue to stir and add ternary composite emulsion, stir for 15 minutes, place in a high-pressure homogenizer, control the homogenization pressure to 10.5MPa, the homogenization speed to 4700rpm, perform high-pressure homogenization for 12 minutes, cool to room temperature, and obtain a cationic fluorine-free oil repellent.
[0067] Among them, the weight ratio of food-grade paraffin, cationic starch, deionized water and ternary composite emulsion is 35:12.6:66:7.8.
[0068] The present embodiment also provides a fluorine-free oil repellent prepared by the aforementioned preparation method. After product qualification testing, the fluorine-free oil repellent of the present embodiment has an active ingredient content greater than 35wt%, a viscosity (25°C) ≤300mPa·s, and a pH (25°C) in the range of 3.0-6.0.
[0069] This embodiment also provides the use of the aforementioned fluorine-free oil-proofing agent in pulp molding manufacturing, specifically, the aforementioned fluorine-free oil-proofing agent is mixed with pulp molding slurry to prepare pulp molding.
[0070] The added weight of the fluorine-free oil-proofing agent is 1.1% of the weight of the pulp molding slurry.
[0071] Example 3
[0072] This embodiment provides a method for preparing a fluorine-free oil repellent, specifically:
[0073] 1. Preparation of modified fillers
[0074] Zirconium nitrate pentahydrate and copper nitrate trihydrate are added to deionized water, stirred and dissolved, and then calcium carbonate and montmorillonite are added and stirred for 20 minutes to obtain a first dispersion; trimesic acid is added to anhydrous ethanol, stirred and dissolved to obtain a second dispersion; the first dispersion and the second dispersion are added to a high-pressure reactor, the high-pressure reactor is sealed, the temperature is raised to 75°C with stirring, the reaction is kept stirring for 5 hours, and then naturally cooled to room temperature, and solids are obtained by centrifugation; the solids are washed with anhydrous ethanol and deionized water, placed in a vacuum thermostat, and activated at 130°C for 6 hours under a vacuum degree of 0.03MPa to obtain a primary modified filler; the primary modified filler is added to 45 times the weight of a glutaraldehyde aqueous solution (concentration of 4.8wt%), ultrasonically treated for 40 minutes under room temperature, and solids are obtained by centrifugation, and the solids are washed with deionized water and dried to obtain a modified filler.
[0075] Among them, in the first dispersion, the weight ratio of zirconium nitrate pentahydrate, copper nitrate trihydrate, deionized water, calcium carbonate and montmorillonite is 1.2:3.7:105:7.5:4.2.
[0076] In the second dispersion, the weight ratio of trimesic acid to anhydrous ethanol is 4.1:105.
[0077] The weight ratio of the first dispersion liquid to the second dispersion liquid is 1:1.1.
[0078] The ultrasonic treatment frequency was 22KHz and the ultrasonic treatment intensity was 13W / cm 2 , the ultrasonic treatment power is 400W.
[0079] 2. Binary composite treatment
[0080] The modified filler and emulsifier OP-10 were added to deionized water, stirred for 30 minutes, then heated to 70°C with stirring, and butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide and vinyltriethoxysilane were added with stirring while keeping warm. After keeping warm and stirring for 20 minutes, a 6wt% aqueous solution of ammonium persulfate was added dropwise. After the addition was completed, the reaction was continued with keeping warm and stirring for 3.5 hours to obtain a binary composite emulsion.
[0081] Wherein, the weight ratio of modified filler, emulsifier OP-10, deionized water, butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide, vinyl triethoxysilane and ammonium persulfate aqueous solution is 17:2.8:85:15:10.5:3.5:6:12.
[0082] 3. Ternary composite treatment
[0083] The modified chitosan was added into 130 times the weight of the binary composite emulsion, and the temperature was raised to 45°C with stirring, and the temperature was kept constant; the ultrasonic frequency was controlled to 28KHz, the ultrasonic power was 400W, the stirring speed was 80rpm, and the ultrasonic stirring reaction was carried out for 6 hours to obtain the ternary composite emulsion.
[0084] The preparation method of modified chitosan is as follows: chitosan with a viscosity-average molecular weight of 400,000 is put into an acetic acid aqueous solution with a volume concentration of 1.5%, and after stirring to dissolve, the mixture is heated to 50°C in a nitrogen atmosphere and kept warm; potassium persulfate is added, and the mixture is stirred and kept warm for 10 minutes; then trimethylammonium glycidyl chloride and N-vinylformamide are added simultaneously, and the mixture is stirred and kept warm for 6 hours to obtain a reaction solution; acetone with a volume of 70% of the reaction solution is added under stirring, and stirring is continued for 30 minutes, and solid matter is obtained by centrifugation; the solid matter is washed with deionized water, and then placed in a vacuum thermostat, and dried to constant weight at 85°C under a vacuum degree of 0.09 MPa to obtain modified chitosan.
[0085] The weight ratio of chitosan, acetic acid aqueous solution, potassium persulfate, glycidyl trimethylammonium chloride and N-vinylformamide is 2.2:110:0.8:3.5:2.6.
[0086] 4. Mixed preparations
[0087] Heat food-grade paraffin until it is completely melted to obtain molten food-grade paraffin for standby use; add cationic starch into deionized water, stir and heat to 75°C, keep warm and stir for 30 minutes, stir and add molten food-grade paraffin, keep warm and stir for 50 minutes, continue to stir and add ternary composite emulsion, stir for 20 minutes, place in a high-pressure homogenizer, control the homogenization pressure to 11MPa, the homogenization speed to 5000rpm, perform high-pressure homogenization for 15 minutes, cool to room temperature, and obtain a cationic fluorine-free oil repellent.
[0088] Among them, the weight ratio of food-grade paraffin, cationic starch, deionized water and ternary composite emulsion is 36:13:67:8.
[0089] The present embodiment also provides a fluorine-free oil repellent prepared by the aforementioned preparation method. After product qualification testing, the fluorine-free oil repellent of the present embodiment has an active ingredient content greater than 35wt%, a viscosity (25°C) ≤300mPa·s, and a pH (25°C) in the range of 3.0-6.0.
[0090] This embodiment also provides the use of the aforementioned fluorine-free oil-proofing agent in pulp molding manufacturing, specifically, the aforementioned fluorine-free oil-proofing agent is mixed with pulp molding slurry to prepare pulp molding.
[0091] The added weight of the fluorine-free oil-proofing agent is 1.2% of the weight of the pulp molding slurry.
[0092] Comparative Example 1
[0093] The technical scheme of Example 2 is adopted, but the differences are as follows: 1) in the step of preparing the modified filler, calcium carbonate and montmorillonite are mixed evenly and then directly treated with an aqueous glutaraldehyde solution; 2) in the ternary composite step, the preparation of modified chitosan is omitted, and unmodified chitosan is added to the binary composite emulsion to prepare the ternary composite emulsion.
[0094] Comparative Example 2
[0095] The technical scheme of Example 2 is adopted, but the differences are as follows: 1) in the step of preparing the modified filler, the addition of zirconium nitrate pentahydrate is omitted, and the treatment of the primary modified filler with glutaraldehyde aqueous solution is omitted, and the primary modified filler is directly used in the subsequent steps; 2) in the binary composite treatment step, the addition of N,N-dimethylmethacrylamide and vinyltriethoxysilane is omitted.
[0096] The weight of the fluorine-free oil-proofing agent added was controlled to be 1.1% of the weight of the pulp molding slurry. The fluorine-free oil-proofing agents of Examples 1-3 and Comparative Examples 1-2 were mixed with the pulp molding slurry, and then pulp molding was performed; the thickness was 0.8 mm and the basis weight was 400 g / m 2 The pulp molded products were placed in an environment with a temperature of 25°C and a relative humidity of 50%. After standing for 24 hours, the ring crush strength index, Taber stiffness, bursting index and tightness of each pulp molded product were tested; and the Kit oil resistance grade, oil contact angle and hot oil penetration resistance of the pulp molded products were measured.
[0097] Among them, the test of the ring crush strength index of pulp molded products refers to the standard GB / T 2679.8-2016 "Determination of ring crush strength of paper and paperboard"; the test of Taber stiffness refers to the standard GB / T 22806-2008 "White cardboard"; the test of bursting index refers to the standard GB / T 454-2020 "Determination of bursting resistance of paper"; the test of tightness refers to the standard GB / T451.3-2024 "Determination of thickness of paper and paperboard".
[0098] For the test of Kit oil resistance level, please refer to TAPPI 559Cm-02 "Testing for Grease and Grease Resistance of Paper and Paperboard".
[0099] The oil contact angle detection method refers to the relevant content of ASTM D 724 "Test method for wettability of paper surface (contact angle method)". Specifically, each pulp molded product is cut into a flat specimen piece with a size of 10 mm × 15 mm, fixed on a clean glass slide with double-sided tape, and the static contact angle of castor oil on the outer surface of each specimen piece is measured using a contact angle tester.
[0100] The hot oil penetration resistance was determined by using a glass pipette to absorb hot oil at 150°C and dripping it into each pulp molded product. The product was allowed to stand for 120 minutes and the pulp molded products were observed to see if there was any hot oil penetration.
[0101] The specific results are shown in the following table:
[0102]
[0103] Furthermore, pulp molded products (thickness 0.8 mm, basis weight 400 g / m 2 ) was filled with hot oil at a temperature of 120°C, and then placed in a 120°C temperature environment. After standing at a constant temperature for 8 hours, the pulp molded products were observed to see if they had thermal deformation. At the same time, the pulp molded products (thickness 0.8mm, basis weight 400g / m 2 ) Placed in a 150°C temperature environment, kept at constant temperature for 24 hours, observe whether each pulp molded product has thermal deformation, and after cooling to room temperature, test the ring crush strength index, Taber stiffness, bursting index, tightness, Kit oil resistance grade, and oil contact angle of each pulp molded product. The specific results are shown in the following table:
[0104]
[0105] Furthermore, the weight of the fluorine-free oil-proofing agent added was controlled to be 1.1% of the weight of the pulp molding slurry. The fluorine-free oil-proofing agents of Example 2 and Comparative Example 1-2 were mixed with the pulp molding slurry and then left to stand for 8 hours. Then, pulp molding was performed to prepare a 0.8 mm thick paper with a basis weight of 400 g / m 2 After the pulp molded products were placed in an environment with a temperature of 25°C and a relative humidity of 50%, after standing for 24 hours, the tensile strength, bursting index, tightness, Kit oil resistance grade, oil contact angle, and hot oil penetration resistance of each pulp molded product were tested. The specific results are shown in the following table:
[0106]
[0107] It can be seen that in the preparation method of the fluorine-free oil-proofing agent of Examples 1-3, in the step of preparing the modified filler, the fluorine-free oil-proofing agent filler component (calcium carbonate, montmorillonite) is used in combination with a zirconium source and a copper source to prepare a zirconium-doped HKUST-1 material, and after obtaining a primary modified filler composited with the filler component and the zirconium-doped HKUST-1 material by an in-situ composite method, the primary modified filler is subjected to aldehyde group modification to obtain a modified filler; the filling effect of the modified filler on the voids of the pulp molded product after the composite, and the combination of the modified filler and the pulp molded product, promotes the formation of a dense barrier layer of the fluorine-free oil-proofing agent; and at the same time, improves the pores of the fiber network of the pulp molded product by the fluorine-free oil-proofing agent. The stability of the filler is improved, the thermal stability and physical properties of pulp molding are improved; and the reaction and bonding performance of the modified filler with other components in the subsequent steps is improved by aldehyde modification; then in the binary composite treatment step, the modified filler, silicon source (vinyl triethoxy silane) and cross-linking monomer (N, N-dimethyl methacrylamide) are used in the polymerization preparation of polyacrylate emulsion, and the aldehyde groups on the surface of the modified filler are reacted and composited with polymer macromolecules, and the adsorption and interface effects of the modified filler on the polymer macromolecules are further improved. At the same time, the silicon source (vinyl triethoxy silane) and the cross-linking monomer (N, N-dimethyl methacrylamide) are combined to form a polyacrylate emulsion. The invention discloses a novel ternary composite emulsion comprising a polyacrylamide (CPA) and a polyacrylate emulsion, and the modification effect of CPA on the polyacrylate emulsion is further improved, so as to further improve the cross-linking film-forming and bonding performance of the binary composite emulsion on the surface of each fiber inside the pulp molding, further improve the oil-proof performance after application, and improve the weather resistance and structural stability of the pulp molding products, avoid the problems of thermal deformation and thermal physical property degradation, and improve the application stability of the fluorine-free oil-proof agent in the slurry; then in the ternary composite treatment step, after the chitosan is modified by using a specific cationic monomer and a non-ionic monomer, the modified chitosan is contacted with the binary composite emulsion, and through chemical bonding and electrostatic action, it is further compounded into a ternary composite emulsion, and further improved. The barrier and oil-proof properties of the fluorine-free oil-proof agent are high; and the thermal stability and structural stability of the pulp molded products are improved by combining modified chitosan with the aforementioned binary components; finally, the ternary composite emulsion is used in combination with paraffin and starch to prepare the fluorine-free oil-proof agent. The aforementioned technical means cooperate and work synergistically with each other to effectively improve the bonding performance of the fluorine-free oil-proof agent with the pulp molding slurry, while improving the oil-proof properties of the pulp molded products after application, avoiding its thermal deformation problem, being able to preserve good physical properties in a high temperature environment or after contact with high temperature food, and improving the high temperature oil-proof properties of the pulp molded products; and improving the application stability of the fluorine-free oil-proof agent in the slurry.
[0108] It can be seen from Comparative Example 1 that after omitting the filler component in the preparation of the modified filler and compounding with the zirconium-doped HKUST-1 material, and replacing the modified chitosan with unmodified chitosan in the ternary composite, on the one hand, it is impossible to improve the thermal stability and physical properties of the pulp molded product by the fluorine-free oil repellent through the thermal stabilization and strengthening effect of the zirconium-doped HKUST-1 material; on the other hand, it is impossible to further enhance the barrier and oil-proof performance of the fluorine-free oil repellent by combining the modified chitosan with the specific cationic and non-ionic monomers, and the stable binding performance with the pulp molding slurry is reduced, and the application of stable The performance is as follows: the physical properties and oil-proof properties of the pulp molded products prepared by using the fluorine-free oil-proof agent of Comparative Example 1 are significantly deteriorated; at the same time, the pulp molded products are thermally deformed when in contact with hot oil or in a high-temperature environment, and the physical properties and oil-proof properties of the pulp molded products are deteriorated to a certain extent; and the stable bonding performance of the fluorine-free oil-proof agent and the pulp molding slurry is reduced. After the mixed slurry is stored for 8 hours, the performance of the fluorine-free oil-proof agent decays, and the oil-proof property and physical properties of the prepared pulp molded products are significantly deteriorated.
[0109] It can be seen from Comparative Example 2 that after omitting the zirconium source doped modified HKUST-1 material and the aldehyde modification treatment in the preparation of the modified filler; and omitting the addition of the silicon source (vinyl triethoxysilane) and the cross-linking monomer (N, N-dimethyl methacrylamide) in the binary composite treatment, the thermal stability and physical properties of the pulp molded products and the binding performance of the fluorine-free oil-proof agent with the pulp molding slurry are reduced; specifically, the physical properties and oil-proof properties of the pulp molded products prepared using the fluorine-free oil-proof agent of Comparative Example 2 are deteriorated to a certain extent; at the same time, the pulp molded products are thermally deformed after contacting hot oil, and the physical properties and oil-proof properties of the pulp molded products are deteriorated to a certain extent; and the stable binding performance of the fluorine-free oil-proof agent with the pulp molding slurry is reduced, and after the mixed slurry is stored for 8 hours, the performance of the fluorine-free oil-proof agent decays, and the oil-proof performance and physical properties of the prepared pulp molded products are deteriorated to a certain extent.
[0110] Unless otherwise specified, all percentages used in the present invention are by mass.
[0111] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a fluorine-free oil-proofing agent, characterized in that: The method comprises the following steps: preparing modified filler, binary composite treatment, ternary composite treatment, and mixed preparation; The method for preparing the modified filler comprises: adding zirconium nitrate trihydrate, copper nitrate trihydrate, calcium carbonate and montmorillonite into deionized water, dispersing them uniformly, and obtaining a first dispersion; adding trimesic acid into anhydrous ethanol, dispersing them uniformly, and obtaining a second dispersion; mixing the first dispersion and the second dispersion, heating them in a sealed environment, keeping them warm for reaction, separating and obtaining a solid, washing and drying the solid, and obtaining a primary modified filler; adding the primary modified filler into a glutaraldehyde aqueous solution, ultrasonically treating them at room temperature, separating and obtaining a solid, and washing and drying the solid, and obtaining a modified filler; The binary composite treatment method comprises the following steps: adding the modified filler and the emulsifier OP-10 into deionized water, dispersing them uniformly, stirring and heating them to 65-70° C., adding butyl acrylate, methyl methacrylate, N,N-dimethylmethacrylamide, and vinyltriethoxysilane while maintaining the temperature, stirring them uniformly, dropping an aqueous solution of ammonium persulfate into them, and maintaining the temperature for reaction to obtain a binary composite emulsion; The ternary composite treatment method is to add the modified chitosan into the binary composite emulsion, raise the temperature to 42-45° C., and react by ultrasonic stirring to obtain the ternary composite emulsion; The preparation method of the modified chitosan comprises the following steps: putting chitosan into an acetic acid aqueous solution, heating it to 45-50° C., adding glycidyl trimethylammonium chloride and N-vinyl formamide in the presence of potassium persulfate, keeping the temperature for reaction, adding acetone for precipitation, separating and obtaining a solid, washing and drying the solid to obtain the modified chitosan; The mixed preparation method comprises the following steps: mixing food-grade paraffin, cationic starch, deionized water and a ternary composite emulsion, and homogenizing the mixture to obtain a fluorine-free oil-proofing agent.
2. The method for preparing the fluorine-free oil-proofing agent according to claim 1, characterized in that: In the preparation of the modified filler, the first dispersion and the second dispersion are mixed and the heat preservation reaction temperature is 70-75°C, and the heat preservation reaction time is 4-5h; In the first dispersion, the weight ratio of zirconium nitrate trihydrate, copper nitrate trihydrate, deionized water, calcium carbonate and montmorillonite is 1.1-1.2:3.5-3.7:100-105:7-7.5:4-4.2; In the second dispersion, the weight ratio of trimesic acid to anhydrous ethanol is 3.9-4.1:100-105; The weight ratio of the first dispersion to the second dispersion is 1:1-1.
1.
3. The method for preparing the fluorine-free oil-proofing agent according to claim 1, characterized in that: In the preparation of the modified filler, the weight ratio of the primary modified filler to the glutaraldehyde aqueous solution is 1:40-45; The concentration of the glutaraldehyde aqueous solution is 4.5-4.8wt%; The ultrasonic treatment frequency is 20-22KHz and the ultrasonic treatment intensity is 12-13W / cm 2 , the ultrasonic treatment power is 350-400W, and the ultrasonic treatment time is 30-40min.
4. The method for preparing the fluorine-free oil-proofing agent according to claim 1, characterized in that: In the binary composite treatment, the weight ratio of the modified filler, the emulsifier OP-10, the deionized water, the butyl acrylate, the methyl methacrylate, the N,N-dimethylmethacrylamide, the vinyl triethoxysilane, and the ammonium persulfate aqueous solution is 16-17:2.5-2.8:80-85:14-15:10-10.5:3.2-3.5:5.7-6:10-12; The concentration of the ammonium persulfate aqueous solution is 5-6wt%; The heat preservation reaction time is 3-3.5h.
5. The method for preparing the fluorine-free oil-proofing agent according to claim 1, characterized in that: In the ternary composite treatment, the weight ratio of the modified chitosan to the binary composite emulsion is 1:120-130; The ultrasonic frequency in the ultrasonic stirring reaction is 25-28KHz, the ultrasonic power is 350-400W, the stirring speed is 70-80rpm, and the ultrasonic stirring reaction time is 5-6h.
6. The method for preparing the fluorine-free oil-proofing agent according to claim 1, characterized in that: In the preparation of the modified chitosan, the viscosity average molecular weight of the chitosan is 300,000-400,000; The volume concentration of acetic acid aqueous solution is 1.2-1.5%; The weight ratio of chitosan, acetic acid aqueous solution, potassium persulfate, glycidyl trimethylammonium chloride and N-vinyl formamide is 1.9-2.2:100-110:0.7-0.8:3.2-3.5:2.4-2.
6.
7. The method for preparing the fluorine-free oil-proofing agent according to claim 1, characterized in that: In the mixed preparation, the weight ratio of food-grade paraffin, cationic starch, deionized water and ternary composite emulsion is 33-36:12-13:64-67:7-8.
8. The method for preparing the fluorine-free oil-proofing agent according to claim 1, characterized in that: In the mixed preparation, the homogenization pressure is 10-11 MPa, the homogenization speed is 4500-5000 rpm, and the homogenization time is 10-15 min.
9. A fluorine-free oil-proofing agent, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. Use of the fluorine-free oil repellent according to claim 9, characterized in that: Application of the fluorine-free oil-proofing agent in pulp molding manufacturing.
Citation Information
Patent Citations
Fluorine-free waterproof and oil-proof agent as well as preparation method and application thereof
CN114086421A
Fluorine-free waterproof and oil-proof agent used in paper pulp molding pulp and use method of fluoride-free waterproof and oil-proof agent
CN114164704A
Cited By
Low-temperature-resistant fluoride-free oil-proofing agent, composition, paper pulp molded product and preparation method of low-temperature-resistant fluoride-free oil-proofing agent
CN120158954A
Low temperature resistant, fluorine-free, oil repellent agent, composition, pulp molded article and method of making
CN120158954B